The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.actbio.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Marine hydroid perisarc: A chitin- and melanin-reinforced composite with DOPA–iron(III) complexes

Abstract: a b s t r a c tMany marine invertebrates utilize biomacromolecules as building blocks to form their load-bearing tissues. These polymeric tissues are appealing for their unusual physical and mechanical properties, including high hardness and stiffness, toughness and low density. Here, a marine hydroid perisarc of Aglaophenia latirostris was investigated to understand how nature designs a stiff, tough and lightweight sheathing structure. Chitin, protein and a melanin-like pigment, were found to represent 10, 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 47 publications
1
22
0
1
Order By: Relevance
“…In Candida albicans, chitin is essential for externalization of melanin (56); in C. neoformans, both chitin synthase (57) and chitosan in the cell wall (44) are reported to modulate melanization. Chitin and melanin have also been reported to interact closely in marine invertebrates (58) and insect wings (59). Hence, the covalent connection between chitin and melanin suggested by this spectroscopic study is supported by, and consistent with, independent observations in animals and fungi showing these components to be closely linked.…”
supporting
confidence: 73%
“…In Candida albicans, chitin is essential for externalization of melanin (56); in C. neoformans, both chitin synthase (57) and chitosan in the cell wall (44) are reported to modulate melanization. Chitin and melanin have also been reported to interact closely in marine invertebrates (58) and insect wings (59). Hence, the covalent connection between chitin and melanin suggested by this spectroscopic study is supported by, and consistent with, independent observations in animals and fungi showing these components to be closely linked.…”
supporting
confidence: 73%
“…If low pH is a precaution limited to Dopa-based protein adhesives, then it may be imposed during adhesion by sandcastle worms (Waite et al 1992), cnidarian hydroids (Hwang et al 2013), turbellarians (Swann et al 1996) and tunicates (Dorsett et al 1987), all of which are known to use Dopa-proteins. If more widely practiced, it may offer a significant potential control point against biofouling that has not previously been considered.…”
Section: Discussionmentioning
confidence: 99%
“…These cross‐links act as an adhesive to the torn body armor of the tunicate. Several hard tissues of organisms such as the jaw of polychaete, the beak of squid, the perisarc of hydroid, and the mandible of grasshopper also utilize catechol and its complex with metal ions for maintaining high stiffness . Moreover, it has been reported that polyphenolic compounds, for example, catechol and tannin derivatives facilitate the spatial nature of HAp crystal growth along the c ‐axis .…”
Section: Introductionmentioning
confidence: 99%